Highly Stable Copper Nanoparticles Linked to Organic Frameworks as Recyclable Catalyst for Three‐Component Click Cycloaddition in Water. Issue 15 (28th September 2016) - Prakash, Sadasivan P.; Gopidas, Karical R.
Abstract: Synthesis, characterization and catalytic applications of highly stable copper‐nanoparticles linked to aromatic frameworks are reported. Synthesis of these nanoparticles was achieved in a one‐pot reaction which involved the simultaneous reduction of CuCl2 .2H2 O and 4, 4'‐biphenylene‐bis‐diazonium tetrafluoroborate using sodium borohydride. Copper atoms formed upon reduction of Cu ions undergo clustering, leading to the formation of copper nanoparticles. At the same time, 4, 4'‐biphenylene‐bis‐diazonium tetrafluoroborate are converted to biphenylene biradicals, which undergoes rapid addition reactions with each other and also on to the nanoparticle surfaces resulting in the formation of aromatic framework linked Cu nanoparticles. Four different types of nanoparticles were prepared by varying the concentration of the metal salts and the ligands. The structure and morphology of these materials were studied using XRD, XPS, SEM and HRTEM analysis. The materials were found to be very good catalysts for click reactions between azides and alkynes and exhibited TOF values as high as 305400 h −1 . They also efficiently catalyzed the one‐pot click reactions involving azide precursors, sodium azide and alkyne. TOF up to 99000 h −1 were observed for these reactions. Abstract : Copper nanoparticles covalently linked to an organic framework prepared in a one step reaction were found to efficiently catalyze the one‐pot multicomponent CuAAC cycloaddition click reactions of azide precursors, sodium azide and alkyne in water. These heterogeneous catalysts can be reused for several cycles.